THE COMPOSITION AND THE CONTENT OF PIGMENTS FROM SOME DYEING PLANT FOR IKAT WEAVING IN TIMORRESE REGENCY, EAST NUSA TENGGARA - Neltji Herlina Ati; Puji Rahayu; Soenarto Notosoedarmo; Leenawaty Limantara (Indonesian Journal of Chemistry, 2006)
Ikat weaving is one of traditional-home industry using plant pigments as a dye which have not been known for their pigments composition. So, the research was carried out to know the composition and the content of pigments in young leaf teak, noni root, turmeric tuber, casuarine bark and betel-nut root. The result showed that pigment composition in young leaf teak consisted of β-carotene, pheophytine, phelargonydine 3-glucosyde, phelargonydine 3,7-diglucosyde, chlorophyllide and two other pigments that have not been identified. Most of the pigments composition in betel-nut root have not been identified, but one of them was condensed tanin. Noni root had pigment composition which consisted of hydrolised tanin, flavonoid and morindon. Pigment composition in turmeric tuber were curcumin, demethoxy curcumin and bis-demethoxy curcumin. Whereas casuarine bark had pigment composition which consisted of delphynidine, cyanydine and phelargonydine. The highest pigment concentration in young leaf teak, betel-nut root, noni root, tumeric tuber and casuarine bark was pheophytine, tanin condensation, morindon, curcumin and cyanidine, respectively.